miR-519 reduces cell proliferation by lowering RNA-binding protein HuR levels - Abdelmohsen, Kotb; Srikantan, Subramanya; Kuwano, Yuki; Gorospe, Myriam (Proceedings of the National Academy of Sciences - PNAS, 2008)
Gene expression is potently regulated through the action of RNA-binding proteins (RBPs) and microRNAs (miRNAs). Here, we present evidence of a miRNA regulating an RBP. The RBP HuR can stabilize and modulate the translation of numerous target mRNAs involved in cell proliferation, but little is known about the mechanisms that regulate HuR abundance. We identified two putative sites of miR-519 interaction on the HuR mRNA, one in its coding region (CR), one in its 3'-untranslated region (UTR). In several human carcinoma cell lines tested, HeLa (cervical), HCT116 and RKO (colon), and A2780 (ovarian), overexpression of a miR-519 precursor [(Pre)miR-519] reduced HuR abundance, while inhibiting miR-519 by using an antisense RNA [(AS)miR-519] elevated HuR levels. The influence of miR-519 was recapitulated using heterologous reporter constructs that revealed a greater repressive effect on the HuR CR than the HuR 3'-UTR target sequences. miR-519 did not alter HuR mRNA abundance, but reduced HuR biosynthesis, as determined by measuring nascent HuR translation and HuR mRNA association with polysomes. Modulation of miR-519 leading to altered HuR levels in turn affected the levels of proteins encoded by HuR target mRNAs. In keeping with HuR's proliferative influence, (AS)miR-519 significantly increased cell number and [(3)H]-thymidine incorporation, while (Pre)miR-519 reduced these parameters. Importantly, the growth-promoting effects of (AS)miR-519 required the presence of HuR, because downregulation of HuR by RNAi dramatically suppressed its proliferative action. In sum, miR-519 represses HuR translation, in turn reducing HuR-regulated gene expression and cell division.